Carbon X-ray absorption in the local ISM: Fingerprintsin X-ray Novae spectra. Issue 2 (11th June 2018) - Gatuzz, Efraín; Ness, J-U; Gorczyca, T W; Hasoglu, M F; Kallman, Timothy R; García, Javier A
ABSTRACT: We present a study of the C K-edge using high-resolution LETGS Chandra spectra of four novae during their super-soft-source (SSS) phase. We identified absorption lines due to C ii Kα, C iii Kα, and C iii Kβ resonances. We used these astronomical observations to perform a benchmarking of the atomic data, which involves wavelength shifts of the resonances and photoionization cross-sections. We used improved atomic data to estimate the C ii and C iii column densities. The absence of physical shifts for the absorption lines, the consistence of the column densities between multiple observations, and the high temperature required for the SSS nova atmosphere modelling support our conclusion about an interstellar medium origin of the respective absorption lines. Assuming a collisional ionization equilibrium plasma the maximum temperature derived from the ratio of C ii /C iii column densities of the absorbers correspond to Tmax < 3.05 × 10 4 K.